Sexuality Relationship in Rokan Hulu Riau with the Al-Quran Approach - Wahidin, Wahidin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Sexuality is a person who uses thoughts, feelings and acts based on his position as a sexual being. The concept of sexuality will differ according to place and time, because it is a social concept and construction of values and behaviors related to sex. This article aims to explain Sexuality and Family Harmonization in Rokan Hulu Riau with the Al-Quran Approach. This research is field research with a qualitative approach, which explains sexuality in the Qur’an and its implications for family harmony in Pekanbaru. The research data collection method uses interviews, observation, documentation, and various articles and books. It was then analyzed using the content analysis method with a descriptive and scientific analysis of a premium message.. The result of this research is that sexuality in Islam is shaped by cultural and religious values. Religious values color the formation of views about what is allowed to be done or not, various imperatives, and attitudes that are developed in relation to gender roles. The view of sexuality in Islam is humanist because it is full of human empathy. Meanwhile, the implications of sexuality on family harmony in Rokan Hulu Riau include; a). Reduced satisfaction with marriage; b). The husband’s self-esteem becomes low in the eyes of the wife; c). Husband feels inferior; d). The husband silences his wife; e). The husband is easily angry with his wife; f). Husband left the house temporarily; g). Cheating husband; and h) Divorce